Relationship between career orientation and leadership motivation of Malaysian youth at public universities - Tiraieyari, Neda; Abdul Hamid, Jamaliah; Abdul Wahat, Nor Wahiza; Omar, Zoharah; Othman, Jamilah; Alby, Jeffrey Lawrence D'Silva (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
The purpose of this paper is to determine the relationship between career orientations and leadership motivation among Malaysian youth. Data were gathered from 711 undergraduate students from four Malaysian public universities. Results showed that certain career orientation correlated significantly with motivation to lead (MTL) with correlation coefficients ranging from 0.1 to 0.4. Among career orientation dimensions, Managerial competency indicated the highest correlation coefficient at 0.48.Results of Regression analysis revealed that managerial competency is the biggest predictor of MTL followed by pure challenge. The findings suggest that not all the career anchors contribute significantly in explaining the variation of MTL. The R2value of 0.279 implies the career anchors explain about 27.9% of the variance/variation in the MTL. The findings from this study could be utilized by policy makers in formulating or developing youth career program.